Highly conductive V4C3Tx MXene-enhanced polyvinyl alcohol hydrogel electrolytes for flexible all-solid-state supercapacitors - Bin, Xiaoqing; Sheng, Minhao; Que, Wenxiu (Frontiers in Chemistry, 2024)
Hydrogel electrolytes are an integral part of flexible solid-state supercapacitors. To further improve the low ionic conductivity, large interfacial resistance and poor cycling stability for hydrogel electrolytes, the V4C3Tx MXene-enhanced polyvinyl alcohol hydrogel electrolyte was fabricated to enhance its mechanical and electrochemical performance. The high-conductivity V4C3Tx MXene (16,465.3 S m−1) bonding transport network was embedded into the PVA-H2SO4 hydrogel electrolyte (PVA- H2SO4-V4C3Tx MXene). Results indicate that compared to the pure PVA-H2SO4 hydrogel electrolyte (105.3 mS cm−1, 48.4%@2,800 cycles), the optimal PVA-H2SO4-V4C3Tx MXene hydrogel electrolyte demonstrates high ionic conductivity (133.3 mS cm−1) and commendable long-cycle stability for the flexible solid-state supercapacitors (99.4%@5,500 cycles), as well as favorable mechanical flexibility and self-healing capability. Besides, the electrode of the flexible solid-state supercapacitor with the optimal PVA-H2SO4-V4C3Tx MXene hydrogel as the solid-state electrolyte has a capacitance of 370 F g−1 with almost no degradation in capacitance even under bending from 0° to 180°. The corresponding energy density for flexible device is 4.6 Wh kg−1, which is twice for that of PVA-H2SO4 hydrogel as the solid-state electrolyte.